“White without Pressure” Associated with Other Degenerations: Features of Vitreoretinal Interface on OCT Scans (Clinical Case) - V. A. Shaimova; T. S. Dmukh; V. N. Trubilin; G. R. Islamova; T. B. Shaimov; E. B. Shklyarov (Oftalʹmologiâ, 2023)
“White without pressure” warrants special attention from ophthalmologists due to the lack of consensus on its etiopathogenesis and associated risk of rhegmatogenous retinal detachment. “White without pressure” appears in various quadrants of the fundus as an area white to gray in color. It is more common in persons with high myopia.The paper presents a clinical case of a 19-year-old male with an association between “white without pressure”, “dark without pressure”, vitreoretinal tuft and symptomatic floaters in the left eye. OCT scanning (SOLIX) was employed to assess the vitreoretinal interface. OCT revealed the intraretinal location of “white without pressure” and “dark without pressure” degenerations without vitreoretinal traction. “White without pressure” degeneration is hyperreflective at the level of the outer retina in the photoreceptor ellipsoid and myoid zones, and “dark without pressure” is hyporeflective at this level. Vitreoretinal tuft is a vitreoretinal degeneration located at the level of the inner limiting membrane. It was detected as a hyperreflective site with vitreoretinal adhesion leading to traction and thickening of the corresponding retinal area. The combination of the three degenerations poses a risk of rhegmatogenous retinal detachment due to the presence of the vitreoretinal tuft.